A penalidade da maternidade no mercado de trabalho brasileiro: uma análise dos efeitos de idade, período e coorte e dos diferenciais socioeconômicos entre mulheres com e sem filhos - Iracy Silva Pimenta (2022)
The objective of this thesis is to analyze, in a comparative perspective, women with and without children in the Brazilian labor market. Specifically, the work aims to i) investigate age, period and cohort effects on hourly wages and labor participation rate of mothers and non-mothers; ii) decompose the average hourly wages gap of both groups, in order to separate the portion explained by productive characteristics from that not explained by attributes; iii) carry out this same decomposition exercise for quantiles of wages distribution. The database used throughout the work was the National Household Sample Survey (PNAD). In order to fulfill the first objective, AgePeriod-Cohort (APC) models were estimated for women aged between 25 and 48 years old, using data from 1992 to 2015. For the other two objectives, it was applied Oaxaca-Blinder and Firpo, Fortin and Lemieux (2009, 2018) models for the decomposition of the wage gap between mothers and non-mothers aged between 25 and 34 years old and between 35 and 44 years old in 2015. Regarding the first objective, the descriptive analysis of age, period and cohort patterns revealed the existence of a motherhood penalty throughout the analyzed age range. However, differences between mothers and non-mothers were attenuated at more advanced ages, due to an improvement in the indicators of mothers, and due to a selectivity effect caused by the migration of women without children to the group with children, in such way that the former group becomes smaller and with specific characteristics. The results of the APC models showed greater importance of age and period effects on hourly wages and labor participation rate of women with and without children, although other combinations of the three dimensions have been found to be relevant, such as age and cohort for labor participation rate, and period and cohort for hourly wages. Regarding the decomposition models for the average wages and quantiles, the results indicated that the attributes of mothers and non-mothers explain most of the income differential between the two groups. Differentials in schooling, weekly hours devoted to household chores and position in occupation constituted the main contributions of the characteristics, while age and the presence of a spouse in household exerted a mitigating effect. For the quantile decompositions, it was observed a greater motherhood penalty at the top of the distribution, which is justified by the higher opportunity cost for high-income women, and the wage rigidity in the lower portion of distribution caused by the minimum wage. In relation to the age perspective, there was a slight reduction in the wage gap between mothers and non-mothers in the oldest age group compared to the youngest. Based on the results, it is concluded that additional studies on childlessness phenomenon in Brazil are necessary in order to better understand the profile of childless women. In addition, it is highlighted the need to share care tasks, so mothers can invest in human capital acquisition, with the participation of public sector, applying policies such as the greater provision of day care services.